How Culture Influences Consumer Loyalty towards Cosmetic Products--A Comparison of UK and Taiwanese consumers - Chen, Hsin-Ping (2007)
Culture is one of the most important factors affecting the marketing department to shape their strategy. This is particularly true when facing global marketing. This project is aimed at examining how the culture influences brand loyalty towards cosmetic products by comparing consumer behaviours of UK and Taiwanese consumers.